ImmUniverse Consortium: Multi-omics integrative approach in personalized medicine for immune-mediated inflammatory diseases - Vetrano, Stefania; Bouma, Gerben; Benschop, Robert J.; Birngruber, Thomas; Costanzo, Antonio; D’Haens, G. R. A. M.; Frasca, Loredana; Hillenbrand, Rainer; Iversen, Lars; Johansen, Claus; Kaser, Arthur; Koenen, Hans J. P. M.; et al. (Frontiers in Immunology, 2022)
Immune mediated inflammatory diseases (IMIDs) are an heterogeneous group of debilitating, multifactorial and unrelated conditions featured by a dysregulated immune response leading to destructive chronic inflammation. The immune dysregulation can affect all organ systems: gut (e.g., inflammatory bowel disease), joint (e.g., rheumatoid arthritis), skin (e.g., psoriasis, atopic dermatitis) resulting in significant morbidity, reduced quality of life, increased risk for comorbidities, and premature death. It is very hard to predict how the disease will develop in a specific patient, and which treatments will be effective, since there are no reliable disease progression nor therapy response biomarkers yet A considerable proportion of patients do not respond sufficiently to treatment. ImmUniverse is a large collaborative consortium of 27 partners that received funding from the Innovative Medicine Initiative (IMI), which is sponsored by the Europen Union (Horizon 2020) and in-kind contributions of participating pharmaceutical companies within the European Federation of Phamaceutical Industries and Associations (EFPIA). ImmUniverse aims to advance the understanding of the molecular mechanisms underlying two immune-mediated diseases, ulcerative colitis (UC) and atopic dermatitis (AD), by pursuing an integrative multi-omics approach. As a consequence of the heterogeneity of IMIDs patients, a comprehensive evidence-based search of novel biomarkers for an appropriate patient stratification that accounts for the inter-individual differences in severity, drug efficacy, side effects or prognosis is necessary and would guide clinicians in the management of patients and represent a major step towards personalized medicine. ImmUniverse will combine the use of existing and novel advanced technologies, including multi-omics, to characterise the tissue microenvironment as well as blood thereby taking advantage of an integrated data storage and analysis platform. The comprehensive, systems biology-orientated analysis of retrospective and prospective clinical samples driven by outstanding omics profiling and computer science-oriented efforts will allow the identification and validation of tissue and circulating biomarker signatures and mechanistic principles that are capable to informe about disease severity and future disease progression. This truly makes the ImmUniverse Consortium an unparalleled approach.